2017
DOI: 10.1371/journal.pbio.2001855
|View full text |Cite|
|
Sign up to set email alerts
|

Viral genetic variation accounts for a third of variability in HIV-1 set-point viral load in Europe

Abstract: HIV-1 set-point viral load—the approximately stable value of viraemia in the first years of chronic infection—is a strong predictor of clinical outcome and is highly variable across infected individuals. To better understand HIV-1 pathogenesis and the evolution of the viral population, we must quantify the heritability of set-point viral load, which is the fraction of variation in this phenotype attributable to viral genetic variation. However, current estimates of heritability vary widely, from 6% to 59%. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 55 publications
4
76
2
1
Order By: Relevance
“…Our study confirms previous studies that established the heritability of the set-point viral load in HIV infection (as reviewed by Müller et al (2011) andFraser et al (2014)). In particular, our estimates are consistent with those from a donor-recipient regression in Hollingsworth et al (2010), and two recent studies applying phylogenetic mixed models based on the Ornstein-Uhlenbeck process by Mitov and Stadler (2016) and Blanquart et al (2017). Our analysis is also consistent with the study by Hodcroft et al (2014) that reported a low heritability of 5.7% of the set-point viral load adjusted for covariates and assuming Brownian trait evolution.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study confirms previous studies that established the heritability of the set-point viral load in HIV infection (as reviewed by Müller et al (2011) andFraser et al (2014)). In particular, our estimates are consistent with those from a donor-recipient regression in Hollingsworth et al (2010), and two recent studies applying phylogenetic mixed models based on the Ornstein-Uhlenbeck process by Mitov and Stadler (2016) and Blanquart et al (2017). Our analysis is also consistent with the study by Hodcroft et al (2014) that reported a low heritability of 5.7% of the set-point viral load adjusted for covariates and assuming Brownian trait evolution.…”
Section: Discussionsupporting
confidence: 89%
“…The recent study by Blanquart et al (2017) also reports heritability of the CD4+ T cell decline. For the HIV-1 subtype B, they estimate a heritability of 11% ranging from 0% to 19%.…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, viral genetic variation may play a more important role in shaping HIV virulence than host factors, with approximately one-third of the observed variability in SPVL assigned to virus factors 111 and only ~13% seemingly due to the host 112 . This observation also implies that SPVL, and hence virulence, can be selectively optimized 113 .…”
Section: Subtype Of Influenza Virusmentioning
confidence: 99%
“…Importantly, however, despite many studies into the determinants of HIV virulence, the virus genomic mutations responsible for determining SPVL are still uncertain and multiple genes may be involved 104 . The difficulty in assigning the genetic determinants of SPVL may be in part due to genetic variation across viral populations 111 . For example, heritability in SPVL was highest (~60%) between individuals in the Swiss HIV cohort, which also represents the most homogenous viral population 113 .…”
Section: Subtype Of Influenza Virusmentioning
confidence: 99%
“…Large-scale sequencing of HIV genomes with NGS using overlapping 2-3 kb PCR amplicons [9] has been used to produce complete genomes for European samples [10], but the method's performance was found to be far from optimal on sub-Saharan African samples, with amplification failures resulting in biased genome coverage [11]. In our previously reported protocol, veSEQ, for Hepatitis C Virus (HCV), a virus which is even more diverse than HIV, we avoided such a genotype-dependent failure rate by avoiding virus-specific PCR altogether [12].…”
Section: Introductionmentioning
confidence: 99%